Found Foto-Film Aneignungen analoger Fotografie im zeitgenössischen Essay- und Dokumentarfilm - Praetorius, Charlotte (Büchner-Verlag, 2022)
In the digital age, we often encounter analog photographs as things that - after having been stored away, lost, or even thrown away - are (re)found. The fascination with such found photographs is reflected in a striking way in contemporary essay and documentary film. Found photo films are an essayistic documentary form that has emerged since the turn of the millennium: Films that work with left-behind, rescued, or found convolutions of photographic images, collecting, selecting, and placing them in a new context. They stand in a field of tension between popular aestheticization and re-auratization of analog media in the course of digitalization as well as a long tradition of cinematically reflecting the materiality and mediality of film by working with photography and found footage. Charlotte Praetorius explores such appropriations of analog photographs through a corpus of international films: How do filmmakers relate to photographic found footage? How do the narratives and the narrativity of photography and history intertwine? How is the photographic material arranged and staged? And how can the relationships between different media and materials be grasped? In doing so, Praetorius is also concerned with taking the forms of documentary and essayistic film seriously as a medium for reflecting on (media) history and at the same time also critically questioning them.